2012
DOI: 10.3109/00498254.2012.669872
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of benzene oxide, a reactive metabolite of benzene, with model nucleophiles and DNA

Abstract: 1. Reactivity of benzene oxide (BO), a reactive metabolite of benzene, was studied in model reactions with biologically relevant S- and N-nucleophiles by LC-ESI-MS. 2. Reaction with N-acetylcysteine (NAC) in aqueous buffer solutions gave N-acetyl-S-(6-hydroxycyclohexa-2,4-dien-1-yl)cysteine (pre-phenylmercapturic acid, PPhMA), which was easily dehydrated in acidic solutions to phenylmercapturic acid (PhMA). The yield of PPhMA + PhMA increased exponentially with pH up to 11% in the pH range from 5.5 to 11.4. 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Previous studies have shown that benzene oxide is relatively unreactive with sulfur nucleophiles and that this pathway occurs at low efficiency compared to rearrangement to phenol at pH 7 [14]. This is also consistent with the studies by Micova and Linhart and with our data indicating the relatively low yields of 7-PhG in reactions of benzene oxide with DNA [8]. …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous studies have shown that benzene oxide is relatively unreactive with sulfur nucleophiles and that this pathway occurs at low efficiency compared to rearrangement to phenol at pH 7 [14]. This is also consistent with the studies by Micova and Linhart and with our data indicating the relatively low yields of 7-PhG in reactions of benzene oxide with DNA [8]. …”
Section: Discussionsupporting
confidence: 93%
“…Applying our method to calf thymus DNA reacted with benzene oxide, we were able to confirm the observations of Micova and Linhart [8] that 7-PhG is produced after treatment of the DNA by either acid or neutral thermal hydrolysis. Our results are consistent with theirs in demonstrating a rather low reactivity of benzene oxide with calf thymus DNA, but direct comparison is difficult because different conditions were used.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous reports suggest that product yield increases under basic conditions, which should increase the nucleophilicity of the thiol and increase the stability of BO in solution [29, 30]. After 30 min, the pH was adjusted to ~2 with 1 N HCl (1.2 mL) in order to dehydrate the intermediate, yielding SPG.…”
Section: Methodsmentioning
confidence: 99%